2015
DOI: 10.1111/risa.12407
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Hurricane Evacuation Intentions

Abstract: Protective actions for hurricane threats are a function of the environmental and information context; individual and household characteristics, including cultural worldviews, past hurricane experiences, and risk perceptions; and motivations and barriers to actions. Using survey data from the Miami-Dade and Houston-Galveston areas, we regress individuals' stated evacuation intentions on these factors in two information conditions: (1) seeing a forecast that a hurricane will hit one's area, and (2) receiving an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
119
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(132 citation statements)
references
References 69 publications
7
119
3
3
Order By: Relevance
“…Some studies have shown that females are significantly more likely than males to reloacte/evacuate (Whitehead et al 2000;Bateman and Edwards 2002;Lazo et al 2015;Lim et al 2016), although Stein et al's (2013) study showed that gender had no significant impact on household evacuation willingness. Some studies have shown that older residents are more likely to relocate/evacuate than other age groups (Lazo et al 2015), but others have found the opposite effect (Kaniasty and Norris 1995;Trumbo et al 2014;Lazo et al 2015) or no effect (Huang et al 2012;Stein et al 2013).…”
Section: Individual Characteristics and Relocation/ Evacuation Willinmentioning
confidence: 96%
See 2 more Smart Citations
“…Some studies have shown that females are significantly more likely than males to reloacte/evacuate (Whitehead et al 2000;Bateman and Edwards 2002;Lazo et al 2015;Lim et al 2016), although Stein et al's (2013) study showed that gender had no significant impact on household evacuation willingness. Some studies have shown that older residents are more likely to relocate/evacuate than other age groups (Lazo et al 2015), but others have found the opposite effect (Kaniasty and Norris 1995;Trumbo et al 2014;Lazo et al 2015) or no effect (Huang et al 2012;Stein et al 2013).…”
Section: Individual Characteristics and Relocation/ Evacuation Willinmentioning
confidence: 96%
“…Clarifying household evacuation and relocation behaviors and the reasons behind them can provide a reference for the formulation of disaster preparedness and mitigation policies, so as to reduce loss of life and property. Most previous studies, however, have centered on developed countries (such as the United States and Canada) (Tobin et al 2011;Durage et al 2014;Lazo et al 2015) and are primarily concerned with urban household response to hurricanes, floods, and other natural disasters (Lim et al 2016), while few studies examine developing countries and the response of rural households in poor areas to geological disasters. Although compared to other natural disasters the impact of landslides does not appear to be particularly high, it is evident that the number of disasters associated with landslides is increasing worldwide (Alcántara-Ayala 2009; Hernández-Moreno and Alcántara-Ayala 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older adults who are unable to evacuate, whether or not they barricade themselves, do not evacuate in response to an evacuation directive (Dostal, 2015). Reporting of individuals suffering from hurricanes affects evacuation intention (Lazo, Bostrom, Morss, Demuth, & Lazrus, 2015). Municipal governments in Japan do not always possess up-to-date information on home-care patients.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, risk perception has shown to affect active behavioral intention, such as in the context of sun blockers and self-examination for melanoma (Rimal & Real 2003) or air pollution and actions related to climate change (Whitmarsh 2008). Also in research on natural hazards, such as hurricanes, risk perception influences behavioral intentions, such as evacuation intentions (Lazo et al 2015). Besides the interest in these active behavioral intentions, communicative behavior is also of high interest.…”
Section: Nature Change Perception -Observation That Nature Is Changingmentioning
confidence: 99%